Synthesis and characterization of supported heteropoly acid: efficient solid acid catalyst for glycerol esterification to produce biofuel additives - Magar, Subhash; Mohanraj, Govindraj T.; Jana, Sumit Kumar; Rode, V, Chandrashekhar (Inorganic and Nano-Metal Chemistry, 2020)
Esterification of glycerol with acetic acid has been studied with different solid acid catalysts, prepared by impregnating phospotungustic, silicotungstic, and phosphomolybdic acids on polymeric material polyvinylpyrrolidone. These results were compared with commercially available montmorillonite KSFO catalyst showed that PVP-DTP gave higher selectivity to di- and triacetins. This study was mainly focused on increasing the selectivity toward triacetin which is an excellent alternative to fossil fuel based fuel additives. The detail characterization was done for the PVP-DTP catalyst which gave complete conversion of glycerol and maximum selectivity of 34% toward triacetin. Complete conversion of glycerol was achieved at 110 degrees C within 6 h of reaction time. The characterization of the catalyst was performed by SEM/EDX, X-ray diffraction, thermogravimetic techniques, and FT-IR analysis.TPD-NH3 characterization showed that DTP supported on PVP increases the catalyst acidity of PVP. The highest acidity of PVP-DTP is also confirmed using NH3-TPD analysis.
Keywords: Glycerol; phospostugustic acid; povidone; solid acid catalyst; triacetin